Microclimate variability and farmers' adaptation strategies - Ong, Siang Eing (Universiti Malaysia Sarawak (UNIMAS), 2014)
Agriculture is relatively sensitive to climatic conditions, and hence is a sector predominantly vulnerable to climate change. This study assessed and compared microclimatic conditions in different land uses, namely oil palm plantations and forests in Bau, Kuching. Generally, oil palm plantations recorded lower relative humidity and soil moisture content, warmer air and soil temperature. Conversely, forests recorded higher relative humidity and soil moisture content, and lower air and soil temperatur~ Trend in soil pH of both land uses was not clear. The microclimate assessment implied that microclimate would be adversely affected if conversion of forests into crop lands continues. Farmers are aware and perceived there were changes of temperature, number of dry days, number of rainy days and trend of onset of hot seasons. Pearson correlation indicated there was a significant association between farmers' perception on number of dry days and occurrences of droughts, and occurrences of floods and number of rainy days. Although farmers experienced climatic variability, adaptation strategies such as crop rotation, cover crops and changing crop varieties are less adopted. Correlation between farmers' perception on changes of temperature and irrigation needs, number of dry days and crop rotation, and occurrences of droughts and changes of pests and disease control efforts were significantly associated. The demographic attributes of farmers such as level of education, age and gender, were found to have no influence on their perceptions on climate variability and their adaptation strategies.